The Eliminator; or, Skeleton Keys to Sacerdotal Secrets - Westbrook, Richard B. (Richard Brodhead) (Salt Lake City, UT : Project Gutenberg, 2012)
"The Eliminator; or, Skeleton Keys to Sacerdotal Secrets" by Richard B. Westbrook is a theological critique written in the late 19th century. This work delves into critical examinations of core doctrines of Christianity, addressing theological dogmas, priesthood authority, and historical narratives of Judaism. Westbrook's intentions appear to challenge long-standing beliefs, particularly the historicity of Jesus and the integrity of religious narratives that have been commonly accepted within Christian traditions. The opening of the book presents a forceful preface that outlines Westbrook's rationale for confronting established theological beliefs, emphasizing skepticism towards traditional views of Jesus as a historical figure. He critiques the clerical authority and the tendency of religious leaders to suppress the truth in favor of protecting their interests. Westbrook passionately asserts that misconceptions and dogmas have led many individuals astray, contending that a significant number of clergy do not genuinely believe in the doctrines they preach. His call for transparency and a push for truth marks the beginning of a broader inquiry into how religions, specifically Christianity and Judaism, have shaped moral understanding and societal constructs, promising an exploration that is both provocative and enlightening for readers interested in religious history and philosophy. (This is an automatically generated summary.)
The whole truth -- Sacerdotalism impeached -- The fabulous claims of Judaism -- Moses and the Pentateuch -- Ancient symbolism and modern literalism -- Astral keys to Bible stories -- The fable of the fall -- Search for the "last Adam" -- What is known of the New Testament -- The drama of the Gospels -- The ideal Christ -- Jesus and other Christs -- A reverent critique on Jesus -- A few fragments -- Blood-salvation -- Things that remain.
Release date is 2012-03-25
David Widger
Keywords: Free thought